From scratch to storyboard: Incorporating techniques for novice users / Wan Salfarina Wan Husain ... [et al.] - Wan Husain, Wan Salfarina; Che Hassan, Siti Hasrinafasya; Nik Kamaruzaman, Nik Nahdiya; Wan Aziz, Wan Adibah Hanis; Wan Abdul Rahman, Wan Fariza (Unit Penerbitan UiTM Kelantan, 2020)
In multimedia, storyboards are utilized as a graphic organizer that comprises of illustrations or pictures showed in sequence to show how a story or plot unfolds and to arrange the scenes. It is a basic method to convey designer ideas to others. However, the development of a storyboard is a regularly neglected part of advanced digital storytelling and it may appear to be a tiresome task for those who involve in multimedia projects and also an illiterate user who has little knowledge of the techniques used to develop a storyboard. These paper objectives intend to give an overview and guidance on the idea of creation, techniques and tools used of a storyboard and its significance for novice users who involve in Multimedia venture. As an outcome, the knowledge of techniques and methods of storyboarding obtained from this paper may help to support novice users to come up with a good storyboard design that utilized some or all the techniques described and acknowledge how important it is to be applied in a multimedia project. This paper will help novice user to comprehend and implement the techniques described to increase their abilities in developing any multimedia project in the future.